Transformative Pedagogy via Digital Technology in Undergraduate Mathematics Education - Bhatt, Krishna Prashad (Academic Journal of Mathematics Education, 2021)
The main purpose of this paper is to review the different papers and theories regarding transformative pedagogy used in mathematics education at the undergraduate level and draw transformative praxis used and unfold the gaps for further research betterment. Also, this paper explores the philosophical theory/idea that guides the transformative pedagogical practices via Digital Technology in education over the globe and analyzes digital boundaries in higher education in Nepal.